Bringing Industry Into The Classroom: Teaching and Learning in Engineering Technology - Nurhidayah, Azmy (Penerbit UMP, 2019)
The education sector worldwide has experience major changes in different aspects throughout the years. These changes are driven by many factors such as globalization, rapid transformation in the industries, current economic development and others. As one of the countries that is moving towards becoming a high-income nation, Malaysia is in the midst of transforming its education sector, from primary and secondary education towards tertiary and higher education.